Impact of Emission Standards on Fine Particulate Matter Toxicity: A Long-Term Analysis in Los Angeles - Mohammad Mahdi Badami; Yashar Aghaei; Constantinos Sioutas (Toxics)
This study examines long-term trends in fine particulate matter (PM2.5) composition and oxidative potential in Los Angeles based on data from the University of Southern California’s Particle Instrumentation Unit, with chemical composition retrieved from the EPA’s Air Quality System (AQS). While regulatory interventions have reduced PM2.5 mass concentration and primary combustion-related components, our findings reveal a more complex toxicity pattern. From 2001 to 2008, the PM2.5 oxidative potential, measured via the dithiothreitol (DTT) assay, declined from ~0.84 to ~0.16 nmol/min/m3 under stringent tailpipe controls. However, after this initial decline, PM2.5 DTT stabilized and gradually increased from ~0.35 in 2012 to ~0.97 nmol/min/m3 by 2024, reflecting the growing influence of non-tailpipe emissions such as brake/tire wear. Metals, such as iron (Fe, ~150 ng/m3) and zinc (Zn, ~10 ng/m3), remained relatively stable as organic and elemental carbon (OC and EC) declined, resulting in non-tailpipe contributions dominating PM2.5 toxicity. Although PM2.5 mass concentrations were effectively reduced, the growing contribution of non-tailpipe emissions (e.g., brake/tire wear and secondary organic aerosols) underscores the limitations of mass-based standards and tailpipe-focused strategies. Our findings emphasize the need to broaden regulatory strategies, targeting emerging sources that shape PM2.5 composition and toxicity and ensuring more improvements in public health outcomes.